Does Social Exclusion Alter Sensory and Pain Thresholds in Children and Adolescents with Functional Abdominal Pain? – Results from a Preliminary Study. Issue 8 (13th December 2018) - Gulewitsch, Marco Daniel; Jusyte, Aiste; Weimer, Katja; Schönenberg, Michael
Abstract: Objective: Functional abdominal pain (AP) is a prevalent issue in childhood and adolescence. The contribution of psychosocial factors in the development and maintenance of this health problem is rather unclear, and experimental studies about underlying mechanisms are lacking. This study investigates whether experimentally induced social exclusion decreases sensory and pain thresholds in children suffering from AP. Subjects: Twenty children/adolescents with AP and 22 healthy controls. Methods: Children/adolescents participated in the Cyberball paradigm, which affects an experience of social exclusion. Thermal sensory and pain thresholds were measured before and after Cyberball. Results: Children/adolescents with AP showed a divergent reaction regarding their sensory threshold after social exclusion: The control group exhibited a tendency toward a decreased sensory threshold whereas the AP group remained stable. Concerning the pain threshold, no effect of social exclusion could be identified. The increase of both thresholds ("numbing") after Cyberball was positively correlated with symptoms of mental health issues. Conclusions: This is the first study to investigate changes in sensory and pain thresholds following painful social interactions in a sample of children/adolescents with a chronic pain condition. Results suggest that AP and control children differ in their reaction of sensory thresholds, which might indicate an altered processing of social exclusion. Replication and further methodological improvements are needed.